Premarital education, socioeconomic conditions, and adolescent knowledge in shaping stunting perceptions among university students in Surakarta with Islamic economics perspectives - Wibowo, Edi; Widajanti, Erni; Wulandari, Rina; Sari, Putri Oktovita; Mustofa, Akhmad (Journal of Islamic Economics Lariba, 2026)
IntroductionStunting prevention is often concentrated on pregnancy and early childhood, although nutritional knowledge, reproductive readiness, and socioeconomic conditions before marriage may influence the health of the family. University students represent an important population whose understanding and perceptions can support early prevention. Evidence integrating premarital education, family socioeconomic factors, adolescent knowledge, and stunting perceptions in an urban Indonesian setting remains limited.ObjectivesThis study examined the association between premarital education and family socioeconomic factors with university students’ knowledge and perceptions of stunting in Surakarta. It also evaluates whether adolescent knowledge mediates these relationships and interprets the findings from an Islamic economic perspective.MethodA quantitative cross-sectional explanatory design was applied to 136 undergraduate students aged 17–25 years from 11 public and private higher-education institutions in Surakarta. Participants were selected using purposive sampling. Data were collected using a structured questionnaire and analyzed using partial least squares structural equation modeling to assess the measurement model, direct relationships, and indirect effects.ResultsPremarital education was positively associated with stunting perceptions and was the strongest predictor of adolescents’ knowledge. Family socioeconomic factors were also positively associated with knowledge and perceptions. Adolescent knowledge positively predicted stunting perceptions and partially mediated the relationships between premarital education and perception, and between socioeconomic conditions and perception. The model explained 44.2% of the variance in adolescent knowledge and 55.5% of the variance in stunting perceptions. These findings indicate that educational exposure, family resources, and cognitive understanding jointly shape prevention-oriented perception.ImplicationsStunting prevention should begin before marriage and pregnancy through coordinated programs involving universities, community health centers, Offices of Religious Affairs, and community institutions. Educational initiatives should be combined with efforts to reduce unequal access to nutritional information, healthcare, and socioeconomic support. From an Islamic economic perspective, such interventions align with the protection of life, progeny, intellect and welfare.Originality/NoveltyThis study contributes an integrated mediation model focusing on university students as a preconception population and extends stunting research by linking behavioral, socioeconomic, and Islamic economic perspectives without claiming direct effects on stunting prevalence.